Inclusion of students with autism spectrum disorder in the Jordanian regular classrooms: Teachers’ perspectives - Sakarneh, Mohammad; Katanani, Hiam; Alrahamneh, Azeez (Specijalna edukacija i rehabilitacija, 2021)
Introduction. This study focuses on the relevance of inclusion for students with autism spectrum disorder (ASD) in the regular classroom. This issue has achieved international recognition with recommendations in most countries that the students should be given the same opportunities as those without disabilities. The case of Jordanian teachers in Amman is selected in this study. Objectives. It specifically aims at investigating the teachers’ perspectives on inclusion of students with ASD in Jordanian regular classrooms. Methods. The issue is evaluated using a qualitative study design where nine teachers were interviewed virtually. Results. The findings indicated the need for better training and skills development in specific aspects and needs of students with ASD. Providing teachers with training as well as materials and financial support is necessary for supporting inclusive learning. The teachers also report significant limitations in how inclusion of ASD students is supported in Jordan. The perspectives towards inclusion of ASD students in Jordan show that they have low confidence and self-esteem in dealing with these students and organizing inclusive classrooms due to inadequate training and experience. Conclusion. The findings of this study indicate the need for policy makers in Jordan to consider providing specific training to their general education teachers.
Keywords: autism spectrum disorder; inclusive education; regular classrooms; teachers’ perspectives